Stress-Induced Changes in the Gastrointestinal Motor System - Victor Plourde (Canadian Journal of Gastroenterology)
Several autonomic, hormonal, behavioural and neuropeptidergic bodily responses to stressful stimuli have been described over the past few decades. Both animal models and human paradigms have been explored. It is acknowledged that stress modulates gastrointestinal (GI) motility through central mechanisms including corticotropin-releasing-factor. This process requires the integrity of autonomic neural pathways. It has become evident that the effects of stress on GI motility vary according to the stressful stimulus, its intensity, the animal species under study and the time course of the study. Recent evidence suggests that chronic or possibly permanent changes develop in enteric smooth muscle properties in response to stress. In animals, the most consistent findings include retardation of gastric emptying in response to various stressors; acceleration of gastric emptying upon cold stress, presumably through the secretion of brain thyroglobulin-hormone; acceleration of intestinal transit; and stimulation of colonic transit and fecal output. In humans, the cold water immersion test has been associated with an inhibition of gastric emptying, while labyrinthine stimulation induces the transition from postprandial to fasting motor patterns in the stomach and the small bowel. Psychological stress has been shown to induce a reduction in the number and amplitude of intestinal migrating motor complexes and to neither affect nor stimulate colonic motility. These various responses to stress are presumably attributed to the preferential activation of specific neuronal pathways under the influence of a given stimulus or its intensity. The significance of these findings and the directions of further studies are discussed.